2^5-3×[3×7-2×(6^2-2^3):4]+1^123
Răspunsuri la întrebare
Răspuns de
5
Răspuns:
12
Explicație pas cu pas:
=32-3[21-2(36-8):4]+1=32-3(21-2 ori 28:4)+1=32-3(21-14)+1= 32-3 ori 7+ 1=32-21+1=12
anastasia5726:
mulțumesc frumos
Răspuns de
4
Răspuns:
Explicație pas cu pas:
2⁵ - 3 x [ 3 x 7 - 2 x ( 6² - 2³ ) : 4 ] + 1¹²³ = 12
= 32 - 3 x ( 21 - 2 x ( 36 - 8 ) : 4 ] + 1 =
= 32 - 3 x ( 21 - 2 x 28 : 4 ) + 1 =
= 32 - 3 x ( 21 - 14 ) + 1 =
= 32 - 3 x 7 + 1 =
= 32 - 21 + 1 =
= 11 + 1 =
= 12
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Studii sociale,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă